2013
DOI: 10.1161/circulationaha.113.002764
|View full text |Cite
|
Sign up to set email alerts
|

Inositol 1, 4, 5-Trisphosphate Receptors and Human Left Ventricular Myocytes

Abstract: Background Little is known concerning the function of inositol 1,4,5-triphosphate receptors (IP3Rs) in the adult heart experimentally. Moreover, whether these Ca2+ release channels are present and play a critical role in human cardiomyocytes remains to be defined. IP3Rs may be activated following Gαq-protein-coupled receptors (GPCR) stimulation affecting Ca2+ cycling, enhancing myocyte performance and, potentially, favoring an increase in the incidence of arrhythmias. Methods and Results IP3R function was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
161
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(167 citation statements)
references
References 49 publications
5
161
1
Order By: Relevance
“…The standard analysis of AP characteristics19, 30 was complemented with a newly developed algorithm for assessment of the repolarization phase.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The standard analysis of AP characteristics19, 30 was complemented with a newly developed algorithm for assessment of the repolarization phase.…”
Section: Resultsmentioning
confidence: 99%
“…Isolated LV myocytes were placed in a bath on the stage of an IX51, IX53, or IX71 (Olympus, Tokyo, Japan) microscopes for patch‐clamp measurements 19, 25, 30, 31. Experiments were conducted at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Although ryanodine receptors (RyRs) are the major cardiac SR/ER Ca 2+ -release channels involved in excitation-contraction coupling (ECC) 17 and ischemia-reperfusion (IR) injury, 18 recent studies reported an increasing role for inositol 1,4,5-trisphosphate receptors (IP 3 Rs) Ca 2+ -release channels in the modulation of ECC and cell death. 19,20 Ca 2+ -handling proteins of ER and mitochondria are highly concentrated at mitochondria-associated ER membranes (MAMs), providing a direct and proper mitochondrial Ca 2+ signaling, including VDAC, Grp75 and IP 3 R1. [20][21][22] Here, we provide evidence that, following IR, a fraction of cellular GSK3β is localized at the SR/ER and MAMs.…”
mentioning
confidence: 99%